Interactive effect of sleep duration and trouble sleeping on frailty in chronic kidney disease: findings from NHANES, 2005–2018 - Xi-Zhe Zhang; Jiong-Ao Xiang; Jun-Jie Xu; Wen-Feng Wang; Yao-Dong Li (Renal Failure)
Background Both sleep disorders and chronic kidney disease (CKD) are recognized as significant public health concerns. In the general population, sleep disorders have been shown to be associated with frailty in the elderly. This study aims to evaluate the association between sleep duration and trouble sleeping with frailty in CKD patients, as well as the potential interactive effect between these two factors.Methods This cross-sectional study analyzed data from the National Health and Nutrition Examination Survey (NHANES) spanning 2005–2018. Sleep duration and trouble sleeping was self-reported. Frailty was assessed using a 49-item frailty index. The associations between sleep duration, trouble sleeping, and frailty were analyzed using weighted multivariate logistic regression and restricted cubic splines. Subgroup analysis was conducted to determine the consistency of the study’s conclusions across various subgroups.Results A total of 5,211 adult CKD patients were included in this analysis. Regression analysis results indicated that short sleep duration (OR = 1.364, 95% CI: 1.152–1.616), long sleep duration (OR = 1.648, 95% CI: 1.259–2.157), and trouble sleeping (OR = 2.572, 95% CI: 2.102–3.147) were significantly associated with an increased risk of frailty in CKD patients, with an interaction between sleep duration and trouble sleeping. Subgroup analysis revealed that the effects of trouble sleeping and sleep duration on frailty symptoms in CKD patients exhibit significant variation across age groups (p < 0.05 for interaction), with no notable differences observed in other subgroups. RCS results demonstrated a U-shaped relationship between frailty and sleep duration, with the lowest risk of frailty at 7.12 h of sleep.Conclusion Our findings indicated that both sleep duration and trouble sleeping were significantly associated with frailty in CKD patients, with a notable interaction between these two factors. Therefore, prevention and intervention strategies for frailty in CKD patients should address multiple aspects of sleep health.